Mechanism of Platelet Hemostasis - Yulduz Salokhiddinovna Khalimova (American Journal of Bioscience and Clinical Integrity, 2025)
Platelets are anucleate cell fragments that play a pivotal role in hemostasis—a complex physiological process aimed at preventing blood loss following vascular injury. Their primary function is to rapidly form aggregates at the site of vascular disruption, thus sealing the injury and protecting the organism from external threats. A key event in this response is platelet activation, characterized by morphological transformation, surface expression of adhesive molecules, release of granular contents, and enhanced interaction with vascular components and other platelets. Despite the lack of a nucleus, platelets exhibit a highly organized internal structure and sophisticated regulatory systems that enable a swift and effective response to vascular injury. This article reviews the morphofunctional features of platelets, the principal stages of platelet hemostasis, molecular mechanisms underlying platelet activation and aggregation, modern diagnostic approaches for assessing platelet dysfunction, and emerging therapeutic strategies.